2017
DOI: 10.1002/jsfa.8515
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishment, identification and aroma compound quantification of Portuguese olive oils based on physicochemical attributes, HS‐GC/MS analysis and voltammetric electronic tongue

Abstract: The preliminary results of this investigation indicate that physicochemical and HS-GC-MS analysis, together with multisensory system coupled with chemometric techniques, presented a satisfactory performance regarding olive oil sample discrimination and identification. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Amongst the available linear pattern recognition approaches [131], Principal Component Analysis (PCA) [91,92,94,95,98,124,132,133], K-Nearest Neighbor (KNN) [134] and Linear Discriminant Analysis (LDA) [97,99,132] features or characteristics of the sample by means of chemometric tools [73]. In some cases, feature extraction strategies or data preprocessing methods must be applied in order to transform an initial larger redundant and complex dataset into a better and reduced data input, which may be achieved by applying pattern recognition tools or variable selection algorithms [130].…”
Section: Data Processing-chemometric Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst the available linear pattern recognition approaches [131], Principal Component Analysis (PCA) [91,92,94,95,98,124,132,133], K-Nearest Neighbor (KNN) [134] and Linear Discriminant Analysis (LDA) [97,99,132] features or characteristics of the sample by means of chemometric tools [73]. In some cases, feature extraction strategies or data preprocessing methods must be applied in order to transform an initial larger redundant and complex dataset into a better and reduced data input, which may be achieved by applying pattern recognition tools or variable selection algorithms [130].…”
Section: Data Processing-chemometric Methodsmentioning
confidence: 99%
“…Still within the scope of olive oils bioactive compounds, Tahri et al [132] showed that a multisensor system combined with chemometric techniques, could be satisfactorily used for olive oil discrimination and identification. These authors used a voltammetric electronic tongue to determine chlorophyll and carotenoids content in olive oils.…”
Section: Electrochemical Evaluation Of Olive Oils Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values are experimentally determined using colorimeters, requiring this additional equipment, if an overall characterization of an olive oil sample is intended. Chlorophylls and carotenoids quantification in olive oil organic extracts, using a voltammetric E-tongue, has been previously reported [30]. Therefore, the possibility of assessing the L*, a* and b* values of the CIELAB scale using the novel potentiometric E-tongue was evaluated for the first time.…”
Section: Colour Scale Cielab Valuesmentioning
confidence: 99%
“…The information concerning the nutritional composition and bioactive compounds for Portuguese PDO olive oils and table oils is very scarce . Notwithstanding, several papers were published with the characterization of Portuguese olive oils and table olives, but for products that are not registered with a EU quality scheme . Therefore, PDO Azeite de Trás‐os‐Montes is the most characterized PDO Portuguese olive oil (Table ).…”
Section: Portuguese Pdo Olive Oils and Table Olivesmentioning
confidence: 99%